Russian Cargo Traffic in New Conditions: Opportunities and Restrictions - M. O. Turaeva (Вестник Российского экономического университета имени Г. В. Плеханова)
The article shows changes that affected cargo operations due to current transformation of the global situation, anti-Russia sanctions and replacement of key economic partners of Russia. The author analyzes accessible data of cargo traffic in home and international lines and explains possible underestimation of certain figures. Restrictions were investigated that hinder the development of some types of traffic, cause losses in cargo operations and shortage of resource capacity, in particular in moving-in and -out. The article shows reasons for impeding further intensive increase in cargo operations. The author studies such restrictions as distance of the route, fuel cost, nature and climatic conditions, the level of road network development, necessity to use transit communication in certain Russian regions, rising rates of utilization duties, high interest rate, risk of trucking companies’ leaving for the green zone, poor experience in using and maintaining Chinese cargo equipment that changed European trucks. The article assessed the dynamics of traffic and prospects of international transit in conditions of further scenario volatility, on the one hand and high adaptive capacity of national economic system to changing conditions and crises, on the other.